(untitled) (Minerva, 2019)
Review: Yorgos Ioanu, El sarcófago, trad. esp. de Amor López, Elisa Ibáñez y Román Bermejo, Valladolid, Servicio de Publicaciones de la Universidad, 1998, 258 pp., ISBN 84-7762-829-7